Arab sojourner expectations, academic socialisation and strategy use on a pre-sessional English programme in Britain. (2nd July 2020) - Hajar, Anas
ABSTRACT: This paper reports on a phenomenographic investigation of Arab sojourners' international academic experiences in terms of their expectations, academic socialisation and their strategy use during a ten-week pre-sessional English language course at a UK university. The qualitative data collected from a written narrative and three subsequent semi-structured interviews revealed how the participants' expectations and strategic learning efforts in the new context were influenced by their learning goals, together with their past language learning experiences. Many held a utopian vision of automatic language development and meaningful interactions with locals once they were in the host environment. The analysis of the data also showed the dominance of highly supportive co-national peers, reluctance to engage in intercultural interactions and a clear preference for "native speaker" tutors. The participants gradually began to identify proximal goals by responding positively to strategies meditated by their writing tutors. They did so because academic writing requirements constitute the main form of assessment in their upcoming postgraduate programmes. The findings of this phenomenographic study have practical implications for the improvement of pre-sessional English courses and also provide directions for future research.